PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SEKOLAH DASAR - Anciliana Ngada; Eka Kartika Silalahi; Paska Sriulina Tarigan; Nova Florentina Ambarwati; Rizky Bastanta B. Manalu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Science and social studies learning in elementary schools still faces challenges related to students’ low learning outcomes due to limited active participation in the learning process. This study aimed to determine the effect of the Numbered Heads Together (NHT) cooperative learning model on the science and social studies learning outcomes of fifth-grade elementary school students. This research employed a quantitative approach with a pre-experimental method using a one-group pretest–posttest design. The sample consisted of 28 fifth-grade students at Sukamaju Catholic Elementary School, Medan Sunggal, selected through total sampling. The research instrument was a learning achievement test administered before and after the implementation of the NHT model. The data were analyzed using descriptive statistics, a normality test, and a paired sample t-test at a significance level of 0.05. The results showed that students’ mean pretest score was 57.3, which increased to 84.7 in the posttest, indicating an improvement of 27.4 points. After the implementation of the NHT model, 22 students, or 79%, achieved the learning objective achievement criteria. The paired sample t-test showed a significance value of 0.000 < 0.05, indicating a significant difference between students’ learning outcomes before and after the treatment. Therefore, the Numbered Heads Together cooperative learning model had a positive and significant effect on fifth-grade students’ science and social studies learning outcomes. This model can be used as an active learning alternative that promotes cooperation, responsibility, and student engagement in understanding science and social studies material.